2023
DOI: 10.1111/nyas.14993
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding links between the microbiome and neurotransmitters

Abstract: The gut microbiota modulates neurobiological activity in various animal lineages. This is often proposed to occur through interactions with neurotransmitters and other neuromodulatory molecules in the host. Our commentary will discuss recent research that establishes microbiota–neurotransmitter connections, gaps in current understanding, and outstanding questions that may guide future advances in the field of microbiota–nervous system interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…An estimated90% of serotonin alone is produced in the gut, primarily from enterochromaffin cells ( 36 ). Many psychopathologies and neurological disorders are associated with disruptions in neurotransmitter levels, which can also act as hormones affecting numerous receptor sites ( 38 ). While still under exploration, it has been shown that bacterial species from the gut microbiota dramatically alter chemicals that mediate neurotransmitters and neural transmission ( 38 ).…”
Section: The Crossroads Of Chronic Stress Immune Activation and The M...mentioning
confidence: 99%
See 2 more Smart Citations
“…An estimated90% of serotonin alone is produced in the gut, primarily from enterochromaffin cells ( 36 ). Many psychopathologies and neurological disorders are associated with disruptions in neurotransmitter levels, which can also act as hormones affecting numerous receptor sites ( 38 ). While still under exploration, it has been shown that bacterial species from the gut microbiota dramatically alter chemicals that mediate neurotransmitters and neural transmission ( 38 ).…”
Section: The Crossroads Of Chronic Stress Immune Activation and The M...mentioning
confidence: 99%
“…Many psychopathologies and neurological disorders are associated with disruptions in neurotransmitter levels, which can also act as hormones affecting numerous receptor sites ( 38 ). While still under exploration, it has been shown that bacterial species from the gut microbiota dramatically alter chemicals that mediate neurotransmitters and neural transmission ( 38 ). Serotonin, which affects both mood and GI function, is the most studied neurotransmitter in the field of psychiatry ( 39 ) and is directly related to microbiota composition ( 38 ).…”
Section: The Crossroads Of Chronic Stress Immune Activation and The M...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies have focused on the influence of various intrinsic and extrinsic factors on the process of personality shaping in animals, including genetics ( Hancock et al, 2019 ), sex ( Gartner and Powell, 2012 ), environment ( Wei et al, 2017 ), and physiology ( Peerboom and Wierenga, 2021 ). For example, changes in neurotransmitter and hormone levels are closely related to animal behavior, and influence the animal personality traits ( Lynch and Hsiao, 2023 ). Given that gut microbes can produce a wide range of neuroactive chemicals and can also modulate the levels of neurotransmitters in the host ( Silva et al, 2020 ; Lynch and Hsiao, 2023 ), the relationship between gut microbiome and animal personality traits has attracted attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…For example, changes in neurotransmitter and hormone levels are closely related to animal behavior, and influence the animal personality traits ( Lynch and Hsiao, 2023 ). Given that gut microbes can produce a wide range of neuroactive chemicals and can also modulate the levels of neurotransmitters in the host ( Silva et al, 2020 ; Lynch and Hsiao, 2023 ), the relationship between gut microbiome and animal personality traits has attracted attention in recent years.…”
Section: Introductionmentioning
confidence: 99%